CalmMind - Kenana Turabi; & Dina Mashayekh (My University, 2024)
CalmMind is a unique mental health support app that uses Flutter, MongoDB, Firebase, and Node.js. It’s designed to provide personalized care by allowing users to choose qualified specialists based on detailed profiles. The app helps users create content, book appointments online, and ensures a secure process for specialists to sign up. It promotes interaction through group chat rooms, creating a supportive space for people facing similar challenges. Administrators are crucial in maintaining the platform’s integrity. They carefully review and approve doctor registrations, sending a confirmation email upon acceptance. CalmMind aims to redefine mental health support by focusing on user interaction, choice, and secure practitioner verification. This versatile app not only sets a new standard for personalized mental health care but also strives to build a community that values user engagement while prioritizing the confidentiality and security of user data.